(untitled) (ENTHYMEMA, 2011)
This article presents some reflections on the concepts, terminology, and epistemological grounds of narrative theory. Our remarks are focused on the proposals advanced at the first RRN conference and they concern in particular two issues: the theoretical difference between classical and postclassical narratology and the paradigms of the contemporary debate. In the first part of the paper we focus on the definitional task of narrative theory; in the second part we describe the epistemology of and the theories built on two opposite paradigms: the mimetic and the constructivist. Our conclusions highlight the continuity and the break points between contemporary theories, soliciting narratologists to answer to the many questions raised.